Hepatitis B virus DNA methylation and its potential role in chronic hepatitis B - Low, Wei Feng *; Ngeow, Yun Fong; Chook, Jack Bee *; Tee, Kok Keng; Ong, Seng Kai *; Peh, Suat Cheng *; Bong, Jan Jin; Rosmawati, Mohamed (Cambridge University Press, 2023)
Hepatitis B virus (HBV) infection led to 66% liver deaths world-wide in year 2015. Thirty-seven per cent of these deaths were the result of chronic hepatitis B (CHB)-associated hepatocellular carcinoma (HCC). Although early diagnosis of HCC improves survival, early detection is rare. Methylation of HBV DNA including covalently closed circular DNA (cccDNA) is more often encountered in HCC cases than those in CHB and cirrhosis. Three typical CpG islands within the HBV genome are the common sites for methylation. The HBV cccDNA methylation affects the viral replication and protein expression in the course of infection and may associate with the disease pathogenesis and HCC development. We review the current findings in HBV DNA methylation that provide insights into its role in HCC diagnosis.